Mangongkal Holi as a Legacy of the Ancient Belief System in the Land of Batak - Angelina Stephani Manullang (Tarikhuna: Journal of History and History Education, 2025)
This research is the result of observing and analyzing the traditional Batak ritual, namely Mangongkal Holi, in Lumban Sinantik, Humbang Hasundutan Regency, North Sumatra. This paper aims to explore and explain the social and cultural values contained in this traditional ritual and how it relates to today's belief systems. During the observation, the author found that this unique ritual has survived and remains deeply ingrained in the Toba Batak people, even though its implementation has been adjusted to the teachings of Christianity. The social and cultural values are still embedded in the ritual, which is why it continues to survive and hold a special meaning for the Toba Batak people. To approach this problem, a historical approach is used and analyzed with qualitative methods. The data was collected through literature studies, interviews, and direct observation of these traditional rituals in the Lumban Sinantik area and was analyzed qualitatively. This paper concludes that this traditional ritual instills solidarity among the descendants of the Batak ethnicity. It serves as a means of strengthening intergenerational relations in the Batak lands and as a historical legacy of the ancient belief system, which has been adapted to include elements of Christianity and Islam